Epidemiological survey of swine influenza A virus in the wild boar population of two Italian provinces. (December 2013) - Foni, Emanuela; Garbarino, Chiara; Chiapponi, Chiara; Baioni, Laura; Zanni, Irene; Cordioli, Paolo
Abstract : Objectives: An epidemiological survey was carried out in order to obtain a better understanding of the role of wild boars in the epidemiology of the influenza virus. Design: The samples were submitted to Real‐Time PCR testing for gene M of the swine influenza virus (SIV), and virus isolation was performed from the positive PCR samples. Genome sequence analysis was performed on the isolates. Additionally, 1, 977 boar sera samples were analyzed using ELISA and hemoagglutination inhibition. Setting: Over recent years, the wild boar population has greatly increased in Italy, including in areas of high‐density industrial pig farming, where the influenza virus is widespread. From July to December 2012, wild boar lung samples were collected in the Parma and Piacenza area, in the Emilia Romagna region. Sample: 354 wild boar lung samples were collected. Main outcome measures: Wild‐boar influenza A virus infection should be studied more broadly in order to obtain a better understanding of the epidemiological role played by this species. Results: Three SIV strains were isolated out of 12 samples that resulted positive using PCR analysis and they were identified as avian‐like SIV subtype H1N1. Phylogenetic analysis of the sequences obtained from isolate A/wild boar/291320/2012 showed that it clustered with recent Italian avian‐like H1N1 SIVs isolated from domestic pigs. Sixty‐eight sera samples showed a positive titer to the isolate A/wild boar/291320/2012. Conclusions: This study suggests that SIV actively circulates in the wild boar population in the investigated. area.